Substance abuse: causes and effects (Mediscope, 2022)
Substance abuse is a rising public health problem especially among young people and a challenge to the family, community and society. It is a complex behaviour seen among young people and it exposes the youth to several physical, medical and psychological consequences. The methods used to abuse these substances could be by drinking, smoking, inhaling, injecting, chewing, sniffing, swallowing, and mixing with food or beverages, or combination of two or more methods; and this can occur in construction sites, hostels, bushy areas, specific spots where illicit substances are sold, hotels and in recreational centres. The prevalence of substance abuse varies from country to country, urban, semi-urban to rural areas. There is a dire need to raise awareness on the effects of substance abuse to young people especially adolescents, and help them adopt positive attitudes, values, behaviours, skills and life-styles that will enable them to contribute maximally to social welfare.Mediscope 2022;9(1): 51-53